치료저항성 우울증의 연구에서 패러다임의 전환 - 김용구; Kim, Yong-Ku (Journal of the Korean Society of Biological Psychiatry, 2016)
Treatment-resistant depression (TRD) is a major public health problem. It is estimated that about 30% of patients with major depressive disorder do not show substantial clinical improvement to somatic or psychosocial treatment. Most of studies for TRD have focused on the subjects already known as TRD. Patients with unipolar depressive episodes that do not respond satisfactorily to numerous sequential treatment regimens were included in the TRD studies. Such post hoc experimental design can be regarded only as consequences of having TRD, rather than as causal risk factors for it. Although informative, data derived from such studies often do not allow a distinction to be made between cause and effect. So, we should shift paradigm toward examining the risk for developing TRD in untreated depressed patients. To deal with this problem, untreated depressed patients should be enrolled in the study to identify biological markers for treatment resistance. The peripheral or central biological markers should be explored before starting treatment. Subsequent systematic administration of treatments with appropriate monitoring in the subjects can determine the risk for developing treatment resistance in untreated individuals. Such information could give a cue to improve the initial diagnosis and provide more effective treatment for TRD.